PENGARUH PROFESIONAL AUDITOR DAN ORIENTASI ETIKA TERHADAP WHISTLEBLOWING DENGAN SENSITIVITAS ETIS SEBAGAI VARIABEL MODERATING - Sofyan Syamsuddin (Jurnal Widya Akuntansi dan Keuangan, 2021)
This study aims to examine the effect of auditor professionalism, ethical orientation, idealism and ethical orientation of relativism towards whistleblowing with ethical sensitivity as a moderating variable. This research is a quantitative study using a descriptive approach. The population in this research are all auditors who work at the Republic of Indonesia Supreme Audit Board. The sampling technique used in this study uses convenience sampling. The sample criteria in this study is that the respondent concerned had at least one audit task, as for the sample in this study amounted to 102 auditors. The data used in this study are primary data collected through a questionnaire survey in physical form and google form. Data analysis using multiple linear regression with the absolute difference value approach. The results of the study with multiple linear regression analysis showed that auditor profesionalisme and ethical orientation in relativism influenced whistleblowing, while the ethical orientation of idealism does not affect whistleblowing. Moderating analysis shows that ethical sensitivity is not able to moderate auditor professionalism, ethical orientation, relativism towards whistleblowing